Differential effect of Pistacia vera extracts on experimental atherosclerosis in the rabbit animal model: an experimental study - Halabalaki Maria; Magiatis Prokopios; Chatziioannou Achilles; Papalois Apostolos; Iliopoulos Dimitrios; Karatzas Theodore; Agrogiannis George; Georgopoulou Katerina; Marinou Katerina A; Tsantila Nektaria; Skaltsounis Leandros A; Patsouris Efstratios; et al. (Lipids in Health and Disease, 2010)
Abstract Background Lipid-enriched diets and oxidative stress are risk factors for the development of atherosclerosis. The effects of the methanolic (ME) and cyclohexane (CHE) extracts of the Pistacia vera nut, often included in the Mediterranean diet, were studied in the rabbit model of atherosclerosis. Methods and results Twenty-four New Zealand White rabbits received atherogenic diet (Control Group), supplemented with ME (Group ME) or CHE (Group CHE) for 3 months. Previously, a GC-MS and a UHPLC LC-DAD-ESI(-)-HRMS/MS method were developed to investigate the extracts' chemical profiles. Blood samples at baseline and monthly determined lipid profile, lipid peroxidation and liver function. The aorta, myocardium and liver were examined histologically at 3 months. Groups ME and CHE had significantly higher HDL- and non-significantly lower LDL-cholesterol median % changes from baseline than the Control Group. Triacylglycerol was significantly higher in Group CHE vs. Control. MDA values were significantly lower in Group ME vs. Control and CHE. ALT and AST were significantly higher in Group CHE vs. Control. γ-GT was lower in Group ME vs. Control. Aortic intimal thickness was significantly less in Groups ME and CHE vs. Control; Group ME atherosclerotic lesions were significantly less extensive vs. Groups Control and CHE. Only Group CHE had significant liver fatty infiltration. Conclusions During short-term administration concomitantly with atherogenic diet, both P. vera extracts were beneficial on HDL-, LDL-cholesterol and aortic intimal thickness. The ME additionally presented an antioxidant effect and significant decrease of aortic surface lesions. These results indicate that P. vera dietary inclusion, in particular its ME, is potentially beneficial in atherosclerosis management.